LITERASI DIGITAL SEBAGAI KATALIS PENGEMBANGAN KOMPETENSI: STUDI POLA PELATIHAN SUMBER DAYA MANUSIA SECARA MANDIRI PADA SISWA DAN PENGUSAHA MUDA - Dinar Nur Febrianti; Tri Marcyanite Waruwu; Wahid Hasim (LAP4B, 2026)
This study explores the role of digital literacy in developing human resource (HR) competencies independently through digital platforms in students and young entrepreneurs. Using a qualitative approach of a case study, the study involved 35 participants (25 vocational school students and 10 young entrepreneurs) at SMK Bintang Nusantara, South Tangerang for six months. Data was collected through in-depth interviews, focus group discussions, and direct observations, then analyzed using thematic analysis. The results showed that: (1) participants utilized various digital platforms (YouTube 96%, Telegram 71%, LinkedIn Learning 60%) with three learning patterns (reactive, proactive, and collaborative); (2) digital literacy plays a crucial role in content validation and curation through five strategies (credibility evaluation, cross-referencing, peer evaluation, practical testing, and continuous learning); (3) the main challenges include information overload (83%), validation difficulties (80%), transfer problems (72%), and lack of learning structure (68%); (4) digital-based HR learning results in a 64% increase in competence in students and a 70% increase in revenue in young entrepreneurs, with a proactive and collaborative learning model showing the greatest impact (75-80% improvement rate). This research makes a significant contribution by presenting a cost-effective and applicable digital-based independent learning model for MSMEs, startups, and educational institutions, while strengthening the understanding of how digital literacy functions as a powerful catalyst for the transformation of limited resources into a competitive advantage for human resources